[Ship Off Dock in Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of a ship along a dock in Heimaey. The black and white ship sits along a dark, stone dock in the foreground. A person uses an orange forklift to haul a stack of brown boxes being supported by another person in a black and white hat. A green, rock covered mountain is visible in the background to the left.